2020
DOI: 10.1097/md.0000000000023380
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a nursing care and follow-up program for patients with heart failure

Abstract: Background: Heart failure (HF) is one of the primary causes of the increasing public health costs, incidence rate and mortality of heart disease. As treatment options for the HF have evolved, people have a better understanding of overall burden of HF, resulting a more centralized method for the treatment of these patients with chronic diseases. At present, with the rapid progress of medical technology, the nursing mode must be updated accordingly. The objective of this trial is to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…HF management interventions are constantly being updated, which also lead to a better understanding of the economic or social burden of HF, thus providing more refined interventions for the treatment of this patient population [ 8 ]. Nursing is one of the indispensable management means, which can provide a certain degree of care for hospitalized patients and help them recover and discharge smoothly [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…HF management interventions are constantly being updated, which also lead to a better understanding of the economic or social burden of HF, thus providing more refined interventions for the treatment of this patient population [ 8 ]. Nursing is one of the indispensable management means, which can provide a certain degree of care for hospitalized patients and help them recover and discharge smoothly [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review focusing on effectiveness of nursing interventions showed that advanced practice nurse interventions imply a reduction in the number of hospital readmissions and an improvement in the quality of life of HF patients (Ordóñez‐Piedra et al, 2021 ). A randomized controlled study showed that nursing care conducted for the HF patients may improve the life quality (Zhang et al, 2020 ). More importantly, outpatient nursing support in HF patients has gradually been valued recently (Kitagawa et al, 2022 ; Østergaard et al, 2021 ; Taniguchi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the China Hypertension Survey (CHS) show that 1.3% of the Chinese adult population aged ≥35 years had HF. It has been emphasized that nurses play an important role in assessing, monitoring, and providing patient care as well as improving outcomes in HF (Bjornsdottir et al, 2021 ; Ordóñez‐Piedra et al, 2021 ; Sezgin et al, 2017 ; Yang et al, 2020 ; Zhang et al, 2020 ). However, more advanced and intensive care means greater burdens on nurses and other care‐givers.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms related to cardiac changes, such as arrhythmia and dyspnea, compromise oxygenation, and HF patients encounter great difficulties regarding what is termed Basic Human Needs (BHN)-breathing, moving, rest and sleep (Pereira et al, 2016). As treatment options for HF have evolved, patients have a better understanding of the overall burden of HF; as such, this has contributed to the development of care methods more adjusted to the needs of these individuals (Zhang, Bai & Huang, 2020). Nursing care is important for people who experience illness; nurses provide patients assistance for making changes in their behavior to achieve good health.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are part of the professional health team who are responsible for helping patients to develop skills to manage their symptoms (e.g., recognize relevant symptoms) and the therapeutic regimen; they promote empowerment, thereby enhancing a patient's well-being and reducing readmissions (Vilas-Boas & Follath, 2006;Zhang et al, 2020). The aim of this study was to identify the most common nursing interventions for assisting with and improving the BHN of patients with HF, including those that promote relief of their symptoms, as well as facilitate their safe care transition from hospital to home.…”
Section: Introductionmentioning
confidence: 99%